ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2016) - Dipanala, Stephani; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2018)
Corporate value is a way to see if the company is in a good position or not. If the company has a good corporate value it shows that the shareholders' position is also in prosperous condition. Corporate value also has a strong influence on stock prices, when the stock price is high then the corporate value is also getting better and if the stock price is low then the corporate value also becomes lowThis research aims to analyze the effect of dividend policy (DPR), debt policy (DER), profitability (ROE), firm size and sales growth of corporate value (PBV) and insider ownership as a control variable.The object of this research refers to manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during the period 2012-2016. The population of this study are 144 manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during 2012-2016.Â The purposive sampling method used was used in selecting the research sample, 94 companies are sampled for the object of this study. Multiple regression technique are chosen for this research statistic analysis. This research founds that debt policy, profitability and size positively and significantly affects corporate value. Dividend policy and sales growth have no significant effect on the dividend payout ratio.